Implemantion of DC-DC Converter for lighting - Winarno, Basuki; Artono, Budi; Triyono, Budi; Pratama, Muhammad Rio (PT FORMOSA CENDEKIA GLOBAL, 2024)
Lighting is still largely dependent on PLN, which can be replaced with sunlight, the electrical energy of which can be stored in batteries. To regulate this electrical energy source, a DC-DC converter is needed. This converter functions to change the voltage according to needs, one of the methods applied is using a bidirectional dc/dc converter. In this method the charging and discharging processes are controlled using proportional integral control analytical methods. Implementation of a bidirectional dc-dc converter for lighting using a DC system is more efficient compared to an AC system because part of the system's power is absorbed by the inverter.